Case report: complete remission with crizotinib in ROS1 fusion-positive sinonasal mucosal melanoma - Cao, Jun; Yu, Yaner; Zhou, Yangkun; Ji, Qing; Qian, Wenkang; Jia, Dongdong; Jin, Gu; Qi, Yajun; Li, Xin; Li, Ningning; Li, Tao; Fang, Meiyu; et al. (Frontiers in Oncology, 2022)
Introduction: Sinonasal mucosal melanoma (SNMM) originates from melanocytes. Currently, the main treatment methods, including surgery, radiotherapy and chemotherapy, have little effect on the recurrence and metastasis of SNMM. However, targeted therapy may be a breakthrough in treating SNMM Methods: A SNMM patient with ROS1 fusion received 200mg Crizotinib capsule (2 times a day, 1 tablet each time) therapy. Results: The patient achieved partial remission after 4 months of treatment and complete remission after 8 months of treatment. Conclusion: Our findings suggest that crizotinib can be an option to improve overall survival and quality of life of patients with metastatic ROS1-fusion SNMM. We believe that our report will provide insights for the application of crizotini in the treatment of melanoma.